5. Measuring Village Unit Cooperative Performance Using Stepwise Discriminant Analysis (A Case of West Lombok Region) - I Gusti Lanang Parta Tanaya (JURNAL AGRIMANSION, 2007)
Abstract Realizing that most Indonesian live in rural areas and use rural business activities as main source income, most of governmental policy released to promote all small business in this area including agriculture. Refers to the national constitution (UUD 1945), cooperative is considered the most suitable business form that can accommodate people interest. In 1978 under presidential instruction most of village unit cooperatives or Koperasi Unit Desa (KUD) were established throughout the nation. However, this business organization is far left behind compared to private owned business and state owned business. Despite, some methods were introduced to evaluate the growth and performance of KUD, until reformation era the situation of this business is still unchanged. This paper tried to use a stepwise discriminant analysis to measure the KUD performance in West Lombok. Financial, organizational, and operational data were collected to support this analysis. Geometric index was applied to identify the performance of KUD. Selected variables were identified to classify individual cooperatives into bad or good performance groups with stepwise discriminant analysis. It is found that the length years of manager run KUD’s business and participation of member doing business with KUD were the two variables that contribute the most significant influence on KUD performance. Abstrak Menyadari bahwa sebagian besar penduduk Indonesia berdomisili di pedesaan dan memanfaatkan aktivitas bisnis pedesaan sebagai sumber pendapatan utama, maka sebagian besar kebijakan pemerintah diluncurkan untuk meningkatkan usaha kecil termasuk bidang pertanian. Merujuk pada UUD 1945, koperasi adalah bangun usaha yang paling cocok untuk mengakomodasi kepentingan penduduk. Tahun 1978, dengan instruksi presiden banyak KUD didirikan di seluruh negara ini. Tetapi perkembangan usaha ini jauh tertinggal dibandingkan dengan usaha milik pemerintah dan usaha swasta. Walaupun banyak cara digunakan untuk mengevaluasi pertumbuhan dan performasi KUD, sampai era reformasi ini keadaannya tidak berubah. Tulisan ini mencoba untuk menggunakan Analysis Diskriminan Berjenjang untuk mengetahui kinerja KUD di Kabupaten Lombok Barat. Data financial, organisasional dan operasional dikumpulkan untuk mendukung analisis ini. Indeks Geometri juga digunakan untuk menghitung kinerja KUD. Dengan menerapkan Analysis Diskriminan Berjenjang variable-variabel terpilih digunakan untuk menggolongkan KUD yang kinerjanya baik dan buruk. Ditemukan bahwa lamanya manager mengelola KUD dan partisipasi anggota dalam usaha KUD adalah dua variabel yang mempengaruhi kinerja KUD paling signifikan.